Epistemology of Digital Marketing in Maritime Leadership: Bridging Intuition and Data-Driven Decision-Making - Adi Juliansyah; Adri Setiawan D.P.; Agung Indra Kusuma; Anditalin Anggraeni; Adrianus Rian; Bambang Supriyanto (Management Dynamics: International Journal of Management and Digital Sciences, 2025)
The maritime industry, traditionally reliant on intuition and experience-based decision-making, is undergoing a transformation with the increasing adoption of digital marketing strategies. However, the epistemological foundations of this transition remain underexplored, particularly in the context of leadership and strategic decision-making. This research examines how maritime leaders, lecturers, and postgraduate students perceive and integrate data-driven marketing strategies into maritime business management. The study provides original value by addressing the gap in maritime leadership research regarding digital marketing epistemology. Unlike previous studies that primarily focus on technical adoption, this research critically analyzes the philosophical and cognitive frameworks influencing digital marketing decision-making. The primary objective is to explore the extent to which digital marketing decisions in maritime leadership are guided by empirical data rather than intuition. Using qualitative research and descriptive analysis, semi-structured interviews were conducted with maritime experts, lecturers, and postgraduate students. Data were analyzed thematically, categorizing responses into competency development, sustainability, and digital transformation barriers. Findings reveal that while data-driven strategies are acknowledged as valuable, traditional leadership models still dominate. Digital marketing adoption is constrained by limited expertise, regulatory challenges, and skepticism toward analytics. The study concludes that bridging this gap requires integrating epistemological inquiry into maritime education and fostering collaboration between industry and academia. Strengthening digital literacy among maritime leaders is essential for ensuring the sustainable and strategic use of digital marketing in the sector.